Comparison of Microwave-Assisted Extraction to Soxhlet Extraction of Mango Seed Kernel Oil using Ethanol and n-Hexane as Solvents - June Neil G. Balacuit; Jollana Dianne A. Guillermo; Reuben James Q. Buenafe; Allan N. Soriano (ASEAN Journal of Chemical Engineering, 2021)
Mango seed kernel oil was extracted by Soxhlet Extraction (SE) and Microwave-Assisted Extraction (MAE) with ethanol and n-hexane as extraction solvents. To optimize the extraction condition for SE, the temperature was set to 90°C for ethanol and 80°C for n-hexane with varying solvent-to-feed ratios (S/F ratio) of 75/12, 75/10, and 60/6 mL/g. As for MAE, the same S/F ratios were considered. Extraction was done for 5, 10, and 15 minutes with microwave power levels of 120 and 240 W. It was found out that the highest yield per extraction process for SE was: 18.00±0.25 % and 9.38±2.03 % using ethanol and n-hexane, respectively; and 6.69±0.05 % and 4.68±0.06 %using ethanol and n-hexane, respectively for MAE. It was also noted that MAE, with the microwave power level of 120 W has less extraction time for about 15 minutes as compared to SE of 8 hours. Also, the best S/F ratio in this study is 60/6 for all processes. In oil quality determination, the oil extracted was examined through several tests such as FTIR, GC-MS, acid value, % FFA, iodine value, saponification value, and melting point. It was noted that oil extracted in ethanol has a better yield compared to that of n-hexane but the oil extracted using n-hexane would provide superior quality.